Parental Involvement in Early English Literacy: A Parent’s Perceptions - Resky Martiana Ningrum; Yogi Novario Nandes; Elita Damayanti; Lusi Nurhayati (Universitas Sarjanawiyata Tamansiswa, 2025)
The exploration of understanding of how the role of parents is concretely manifested in supporting early English literacy in the home environment, especially in the EFL context, as well as the parental challenges. This study addresses that gap by exploring parental involvement, highlighting flexible, interest-based approaches and emphasizing the significance of home literacy environments (HLE) as conceptual framework. This study utilized a qualitative descriptive approach to provide a comprehensive narrative revealing parents’ involvement during the literacy process. The data obtained twice using semi-structured interviews involving two full time mothers currently enrolled as masters’ students. The data analyzed in Thematic to identify six main aspects consist of physical environment, parental literacy habits, children-parent interaction, children interest engagement, parental beliefs and attitudes, and barriers in parental involvement. Due to the trustworthiness, this study integrates member checking by participants validation and peer debriefing to avoid bias subjectivity. The results of this study reveal that parental involvement practices in flexible, creative, and child-interest based approaches are considered due to parental beliefs in concern on growth of their children. In spite of the time constraints, overload parental role, and children learning motivation inconsistency, the participants exhibited strong commitment to overcome the challenges through parental partnership collaboration and play-based learning. This study highlights the responsive literacy practices in shaping English early literacy in HLE context.